Additional aperture detectors of gamma-telescope GAMMA-400 calibrations on synchrotron "PAKHRA": possibility of temporal profiles fractal analysis. (February 2019) - Arkhangelskaja, I V; Arkhangelskiy, A I; Chasovikov, E N; Suchkov, S I; Runtso, M F; Yurkin, Y T; Galper, A M; Topchiev, N P; Leonov, A A; Egorov, A E
Abstract: GAMMA-400 (Gamma Astronomical Multifunctional Modular Apparatus) will be the new generation satellite gamma-observatory. The gamma-ray telescope GAMMA-400 consists of anticoincidence system (top and lateral sections - ACtop and AClat), the converter-tracker (C), time-of-flight system (two sections S1 and S2), position-sensitive calorimeter CC1, electromagnetic calorimeter CC2, scintillation detectors of the calorimeter (S3 and S4) and lateral detectors of the calorimeter LD.Three apertures provide events registration both from upper and lateral directions. The main aperture provides the best angular (all double (X, Y) tracking coordinate detectors layers information analysis) and energy resolution (energy deposition in the all detectors studying). The main aperture created firstly due to converter-tracker (C): gammas converted in tungsten conversion foils are registered. Triggers in the main aperture will be formed using information about particle direction provided by time of flight system and presence of charged particles or backsplash signal formed according to analysis of energy deposition in combination of both layers anticoincidence systems ACtop and AClat individual detectors. Other two apertures used for observation of transient events do not require best angular resolution as gamma-ray bursts and solar flares both from upper and lateral directions. Additional aperture allows particles registering from upper direction, which don't interact with converter-tracker and don't formed TOF signal. Particles detection in additional aperture starts with signal of CC1 fast discriminators in anticoincidence with TOF. Energy band for gammas registration in this aperture is similar to the main one. In the lateral aperture low energy (0.2-100 MeV) photons classified by using simple anticoincidence signals from the individual detectors of LD and CC2. Higher energies γ-quanta (E>100 MeV) recognized using energy deposition analysis in the individual detectors of S3, S4, LD and CC2. Prototype of additional aperture functioning of GAMMA-400 contains two detectors. One of them AC/LD prototype based on BC-408 scintillator with dimensions of 128x10x1 cm 3 . Other is CC1 prototype composed of CsI(Tl) crystal with dimensions of 33x5x2 cm 3 . The positron beam with energies 100-300 MeV was used for calibration of prototypes of GAMMA-400 detectors on synchrotron "PAKHRA". We calculate fractal dimension of temporal profiles measured during calibrations of AC/LD and CC1 prototypes. Preliminary results are 1.50±0.05 and 1.48±0.08 correspondingly. This is similar to Poisson statistics or Erlang one with coefficient up to 10.